2012
DOI: 10.4049/jimmunol.1003787
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Autoimmune Gastritis in Thymic Stromal Lymphopoietin Receptor-Deficient Mice

Abstract: Thymic stromal lymphopoietin (TSLP), mainly produced by epithelial cells, activates a variety of cell types, including dendritic cells, mast cells, T cells, and B cells. It is involved in the pathogenesis of allergic inflammation in the lung, skin, and gastrointestinal tract. In addition, TSLP promotes Th2-type intestinal immunity against helminth infection and regulates Th1-type inflammation in a mouse model of colitis, suggesting that it plays crucial roles in intestinal immune homeostasis. Although autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In addition, the distribution of TSLP in the thymus was similar to that in keratin 5 þ medullary thymic epithelial cells (mTECs), suggesting that only mTECs express TSLP in the thymus. It has been reported that altered TSLPR expression could lead to reduced Tregs in multiple sclerosis [20] and increased Th1 immune responses in autoimmune gastritis [50]. Indeed, the reduced TSLP expression in atherosclerotic mice in the present study is consistent with less TSLP expression in severely obese men with compared with without the metabolic syndrome [51], in which the precise mechanism has not been elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the distribution of TSLP in the thymus was similar to that in keratin 5 þ medullary thymic epithelial cells (mTECs), suggesting that only mTECs express TSLP in the thymus. It has been reported that altered TSLPR expression could lead to reduced Tregs in multiple sclerosis [20] and increased Th1 immune responses in autoimmune gastritis [50]. Indeed, the reduced TSLP expression in atherosclerotic mice in the present study is consistent with less TSLP expression in severely obese men with compared with without the metabolic syndrome [51], in which the precise mechanism has not been elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have reported the expression and secretion of TSLP from cancer cells in various malignancies among breast, lung, and pancreatic cancers. In both humans and mice, TSLP mRNA expression was found in the intestines, stomach, and esophagus [46]. TSLP mRNA was significantly overexpressed in the intestines of mice and patients with ulcerative colitis, as well as in inflamed esophageal tissues of patients with eosinophilic esophagitis [45,[47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, loss of TSLP signaling in a mouse model of autoimmune gastritis resulted in more severe disease (Nishiura et al, 2012). Although the impact of TSLP on colitis in mice appears more complex (Taylor et al, 2009; Reardon et al, 2011), this supports a model in which loss of TLSP, which can block TH1/TH17 responses, leads to increased inflammation.…”
Section: Tslp-associated Diseasesmentioning
confidence: 99%